2006
DOI: 10.1111/j.1365-2486.2006.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy photosynthesis, evapotranspiration, leaf nitrogen, and transcription profiles of maize in response to CO2 enrichment

Abstract: The effects of CO 2 enrichment on the growth and physiology of maize were investigated at the molecular, biochemical, leaf, and canopy levels. Maize plants were grown in sunlit soil-plant-atmosphere research (SPAR) chambers at ambient (370 lmol mol À1 ) or elevated (750 lmol mol À1 ) atmospheric carbon dioxide concentration (C a ) under wellwatered and fertilized conditions. Canopy gas exchange rates and leaf temperatures were monitored continuously during the growing season. CO 2 enrichment did not enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
99
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 58 publications
19
99
1
4
Order By: Relevance
“…Pn of ear leaf in maize could partly indicate the photosynthetic capacity, thus it is the key factor to determine grain yield (Kim et al, 2006). The value of Pn were significantly reduced by plough pan in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Pn of ear leaf in maize could partly indicate the photosynthetic capacity, thus it is the key factor to determine grain yield (Kim et al, 2006). The value of Pn were significantly reduced by plough pan in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Leakey et al (2004) showed maize growth at elevated [CO 2 ] significantly increased leaf photosynthetic CO 2 uptake rate by up to 41%, and 10% on average. Kim et al (2006Kim et al ( , 2007 (Fig. 5), g c and T T reduced by 26.6% (18.5%) and 44.5% (38.1%) on average, respectively, during the growing period in 2002 with total precipitation 476 mm (1997 with total precipitation 490 mm); L AI and crop yield increased by 0.96% (5.56%) and 3.25% (6.15%) on average, respectively, in 2002 (1997).…”
Section: Crop Response To Elevated [Co 2 ]mentioning
confidence: 99%
“…The important consideration is that experimentally observed crop physiological responses to climate change variables at plot and field levels (e.g. Kimball et al, 1995;Ainsworth et al, 2002;Leakey et al, 2004;Kim et al, 2006Kim et al, , 2007 are too simplified in current crop models (Tubiello et al, 2007a). As a consequence, the potential for negative surprises is not fully explored, thus reducing the level of confidence in regional and global projections (Tubiello et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in field and laboratory chambers have shown a decrease in ET with elevated CO 2 (Chaudhuri et al, 1990;Li et al, 2004;Kim et al, 2006), and others have not (Hileman et al, 1994). However, coupling to the atmosphere, humidity, radiation, and temperature are all altered by chambers, such that they may modify ecosystem response to CO 2 (McLeod and Long, 1999).…”
mentioning
confidence: 99%